Disrupsi: Peluang dan Tantangan Pemasaran - Rini Astuti (Jurnal Manajemen dan Kearifan Lokal Indonesia, 2021)
This research is about industry revolution 4.0 which supports disruption in agriculture and management (advertising). Qualitative method with case study analysis is used in this research, specifically on Mr Basiri case as the subject, who is the condito sine qua non, known for his hidroganic invention. According to the analysis, it can be concluded that, by using YouTube to spread his knowledge, he was able to promote himself and obtain a source of income. Besides earning revenue from YouTube, a lot of people and organizations who are interested in his uploaded videos actually come to meet him or communicate with him through mobile phone to implement his farming model. Everything that had happened unexpectedly made him viewed as unique, as he loves to share, help, think ahead, follow the rules, do continuous research, and live religiously